Cost-effectiveness of six strategies for Helicobacter pylori diagnosis and management in uninvestigated dyspepsia assuming a high resource intensity practice pattern - Jackson Brian R; Fang John C; Holmes Kyland P (BMC, 2010)
Abstract Background Initial assessment of dyspepsia often includes noninvasive testing for Helicobacter pylori infection. Commercially available tests vary widely in cost and accuracy. Although there is extensive literature on the cost-effectiveness of H. pylori treatment, there is little information comparing the cost-effectiveness of various currently used, noninvasive testing strategies. Methods A Markov simulation was used to calculate cost per symptom-free year and cost per correct diagnosis. Uncertainty in outcomes was estimated using probabilistic sensitivity analysis. Results Under the baseline assumptions, cost per symptom-free year was $122 for empiric proton pump inhibitor (PPI) trial, and costs for the noninvasive test strategies ranged from $123 (stool antigen) to $129 (IgG/IgA combined serology). Confidence intervals had significant overlap. Conclusions Under our assumptions for how testing for H. pylori infection is employed in United States medical practice, the available noninvasive tests all have similar cost-effectiveness between one another as well as with empiric PPI trial.